2008
DOI: 10.2340/00015555-0495
|View full text |Cite
|
Sign up to set email alerts
|

Segmentally Arranged Basaloid Follicular Hamartomas with Osseous, Dental and Cerebral Anomalies: A Distinct Syndrome

Abstract: A 39-year-old man presented with multiple basaloid follicular hamartomas involving the right side of his body in a systematized pattern following Blaschko’s lines. His right leg was 22.5 cm shorter than the left, and rudimentary pre-axial polydactyly was noted on the left hand and the right foot. The teeth of the right maxilla were hypoplastic. DNA analysis of blood lymphocytes and fibroblasts from lesional skin did not reveal any mutation in the Patched gene. On account of this case and of 8 similar cases fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Based on this case and eight similar cases previously reported under different designations (unilateral skin lesions associated with multiple neoplasms, nevus comedonicus syndrome, and unilateral linear basal cell and adnexal nevus), they defined the spectrum of a distinct syndrome. 1 The authors concluded that the syndrome represented a mosaic phenotype. Later that same year, Itin reported another similar case and proposed the term Happle-Tinschert syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this case and eight similar cases previously reported under different designations (unilateral skin lesions associated with multiple neoplasms, nevus comedonicus syndrome, and unilateral linear basal cell and adnexal nevus), they defined the spectrum of a distinct syndrome. 1 The authors concluded that the syndrome represented a mosaic phenotype. Later that same year, Itin reported another similar case and proposed the term Happle-Tinschert syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…Lesions present at birth, during childhood or puberty (López Jiménez et al, 2017). Segmental BFH can occur in association with systemic manifestations in Happle‐Tinschert syndrome (HTS), a mosaic disorder characterized by segmental BFH along with skeletal, ophthalmic, and other systemic abnormalities (Happle & Tinschert, 2008, 2016; Lovgren et al, 2020). This syndrome phenotypically overlaps with Curry‐Jones syndrome (CJS; OMIM 601707) found in 2016 to be caused by a recurrent post‐zygotic SMO , c.1234C>T, p.L412F pathogenic variant (Twigg et al, 2016).…”
Section: Introductionmentioning
confidence: 99%